2015
DOI: 10.1007/s00894-015-2710-5
|View full text |Cite
|
Sign up to set email alerts
|

Ligand effects due to resonance character in LAuCCH− (L = F, Cl, Br, I, CCH) complexes: an NBO/NRT analysis

Abstract: The organogold complexes of LAuCCH(-) (L = F, Cl, Br, I, CCH) were investigated using natural bond orbital/natural resonance theory (NBO/NRT) methods. The NBO/NRT results strongly support the general resonance-type three-center-four-electron (3c/4e) picture of LAuCCH: L(-): Au-CCH ↔ L-Au :CCH(-), arising from hyperconjugation interactions. The sums of ionic and covalent contributions to both L-Au and Au-CCH bonds are all slightly larger than that due to the additional π-back bonding within the 3c/4e hyperbonde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Then, what is the Cu/Ag/Au bonding like? Actually, the importance of ω-bonding for Cu/Ag/Au bonding was recognized in our studies from 2015 to 2017. We demonstrated that Cu/Ag/Au bonding is like ω-bonding based on the preliminary analysis of two-resonance structures and their weights. Soon after, Lu et al performed a similar investigation on some XH 2 P–MY complexes, providing additional examples to support our results.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…Then, what is the Cu/Ag/Au bonding like? Actually, the importance of ω-bonding for Cu/Ag/Au bonding was recognized in our studies from 2015 to 2017. We demonstrated that Cu/Ag/Au bonding is like ω-bonding based on the preliminary analysis of two-resonance structures and their weights. Soon after, Lu et al performed a similar investigation on some XH 2 P–MY complexes, providing additional examples to support our results.…”
mentioning
confidence: 71%
“…Nevertheless, on the basis of the natural bond orbital (NBO) and natural resonance theory (NRT) methods, our earlier studies established that the studied Cu/Ag/Au-bonded complex should be better represented as a resonance hybrid of two natural Lewis structures. 16,17 This resonance description exhibits a formal resemblance to H bonding. However, with 21−28 The CS bond belongs to a new class of chemical bonds, emerging from the valent bond (VB) theory, and it is supported by the atoms in molecules (AIM) theory.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…53 On the basis of this result, they proposed that this finding can be extended into any atom (X) in the periodic table that involves intermolecular bonding of D−X•••A complexes. Recent studies in our group extend this conservation concept into Cu/Ag/Aubonding complexes 23,54 and noble-gas hydrides. 22 Here, we discuss the conservation of the bond order in the noble gas− noble metal halides.…”
Section: Covalency Of the Bonding In Ngmxmentioning
confidence: 96%